Effects of dietary supplementation with filamentous microalgae (Oedocladium sp. or Tribonema ultriculosum) on growth performance, fillet fatty acid composition, skin pigmentation, and immune response of yellow catfish Pelteobagrus fulvidraco. Issue 6 (16th August 2021) - Chen, Weijun; Wang, Yu; Han, Danxiang; Han, Dong; Zhu, Xiaoming; Xie, Shouqi; Long, Feiping; Jia, Jing; Hu, Qiang
Abstract: A 40‐day feeding trial was conducted to investigate the effect of dietary microalgae Oedocladium sp. or Tribonema ultriculosum supplementation on growth performance, fillet fatty acid composition, skin pigmentation, and immune response of yellow catfish Pelteobagrus fulvidraco . Two hundred and seventy experimental fish (51.19 ± 1.17 g) were distributed among nine net cages (2 × 2 × 2 m 3 ) in a randomized design and were fed diets containing 0% (control), 4% Oedocladium meal (Oedocladium), and 5% T. utriculosum meal (Tribonema) to apparent satiation twice a day. After the feeding trial, a hypoxic stress test was conducted to evaluate the effect of dietary microalgal supplementation on fish immune response. Compared to the control, microalgal supplementation did not affect fish growth performance. Dietary supplementation of T. utriculosum significantly increased fillet contents of palmitoleic acid by 100.44% and eicosapentaenoic acid by 12.51%, while the supplementation of Oedocladium meal in diet significantly increased the fish skin ventral lutein content by 61.6%. In addition, dietary Oedocladium or T. utriculosum supplementation significantly increased the plasma total superoxide dismutase activity (before hypoxic stress) and complement component 3 contents (after hypoxic stress). The addition of T. utriculosum meal also significantly increased the plasma immunoglobulin M content regardless of hypoxic stress. These results demonstrated Oedocladium sp. and T. utriculosum can be used to enhance fillet nutritional quality, skin pigmentation, and fish immune response.